Experimental determination of rebound coefficient of valve plate with elastomeric elements in piston low-speed compressor stage - I. S. Busarov; V. L. Yusha; S. S. Busarov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Experimental studies of dynamics of the locking element of self-acting valve with elastomeric elements of slow-moving long-stroke stages makes it possible for the first time to obtain a diagram of motion of the valve plate for the compressor units under consideration. The main principal result of the dynamic analysis of the valve is the absence of rebounds from the seat and the lift limiter during motion of the locking element. The data obtained in the future can be used to develop and verify the methodology for calculating such valves